Maintenance of National Values, the Role of Indonesian Language as Nationalism - Marsella Desriyarini Gui; Irmayani Halim (MultiTech Publisher, 2023)
Understanding the position and function of Indonesia can be the basis for fostering a spirit of nationalism among young people and students. In this case, Indonesian has two positions, namely as a national language and a state language. In its position as a national language, the language functions as a symbol of national pride, national identity, a means of communication between citizens, between regions and between cultures, and a means of unifying ethnicity, culture and language in the archipelago. Meanwhile, in its position as a state language, Indonesian functions as an official state language, a language of education, a means of communication at the national level and a tool for developing culture, science and technology. Remembering the importance of the position and function of the Indonesian language, the author invites young people and students to maintain and continue to develop so that the Indonesian language continues to survive and develop in the future